ACT-02 Changes in Recurrence Pattern and Prognosis of Glioblastoma after Approval of Bevacizumab as First-line Application. (28th November 2020) - Funakoshi, Yusuke; Hata, Nobuhiro; Kuga, Daisuke; Hatae, Ryusuke; Sangatsuda, Yuhei; Fujioka, Yutaka; Takigawa, Kosuke; Mizoguchi, Masahiro
Abstract: Introduction: There exist controversies on recurrence and aggressiveness after use of first-line bevacizumab (BEV) which has been approved in Japan and proven to be beneficial. Therefore, we analyzed the clinical impact of BEV approval by investigating the overall clinical course and glioblastoma (GBM) relapse pattern. Methods: We included 100 patients with IDH-wildtype GBM between September 2006 and February 2018 from our institution. They were subdivided into pre-BEV (n=51) and post-BEV (n=49) groups. Overall, progression-free, deterioration-free, and post-progression survivals (OS, PFS, DFS, and PPS, respectively) were compared. We analyzed the relapse pattern of 72 patients, whose radiographic progressions were confirmed. Results: Significant improvements in DFS (median DFS in the pre-BEV and post-BEV eras: 8.5 and 13.8 months, P=0.0046), and PFS (7.5 and 9.9 months, P=0.0153) after BEV approval were observed. These survival prolongations were strongly correlated (r: 0.91, P<0.0001). Non-enhancing tumor emerged as a novel recurrence pattern in the post-BEV era (five of 33; 15.2%). Changes in relapse pattern did not significantly impact OS, PFS, and DFS. No significant difference in PPS between pre-BEV and post-BEV eras was observed (6.7 and 5.5 months, P=0.2319). The rate of early (within 6 months) focal recurrence was significantly lower (P=0.0155) in the post-BEV era (four of 33; 12.1%) than in the pre-BEV era (18 of 39; 46.2%). A significant decrease in early focal recurrence after BEV approval was observed exclusively in patients with unresectable tumors (P=0.0110). Treatment era was the only parameter significantly correlated with decreased early focal recurrence rate (P=0.0021, univariate analysis; P=0.0144, multivariate analysis). Conclusions: We found that, first-line BEV in Japan for unresectable tumors has a positive impact on the prevention of early progression and clinical deterioration of GBM without accelerating the clinical course after recurrence.